2020
DOI: 10.3389/fnhum.2020.585505
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Pitch Labeling: No Evidence for an Impact of Absolute Pitch on Behavioral and Neurophysiological Measures of Cognitive Inhibition in an Auditory Go/Nogo Task

Abstract: Pitch labeling in absolute pitch (AP), the ability to recognize the pitch class of a sound without an external reference, is effortless, fast, and presumably automatic. Previous studies have shown that pitch labeling in AP can interfere with task demands. In the current study, we used a cued auditory Go/Nogo task requiring same/different decisions to investigate both behavioral and electrophysiological correlates of increased inhibitory demands related to automatic pitch labeling. The task comprised two Nogo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…Prior studies using these neural correlates as a metric of Stroop interference effect have shown comparable amplitude modulation in musicians with or without AP ( Itoh et al. 2005 ; Greber and Jäncke 2020 ). Sharma et al.…”
Section: Introductionmentioning
confidence: 94%
“…Prior studies using these neural correlates as a metric of Stroop interference effect have shown comparable amplitude modulation in musicians with or without AP ( Itoh et al. 2005 ; Greber and Jäncke 2020 ). Sharma et al.…”
Section: Introductionmentioning
confidence: 94%